2017
DOI: 10.1140/epjc/s10052-017-5258-y
|View full text |Cite
|
Sign up to set email alerts
|

Search for CP violation effects in the $$h\rightarrow \tau \tau $$ h → τ τ decay with $$e^+e^-$$ e

Abstract: A new method is proposed to reconstruct the neutrinos in the e + e − → Zh process followed by the h → τ τ decay. With the help of a refined Higgs momentum reconstruction from the recoiling system and the impact parameters, high precision in the determination of the momentum of neutrinos can be achieved. The prospect of measuring the Higgs CP mixing angle with the h → τ τ decay at e + e − colliders is studied with the new method. The analysis is based on a detailed detector simulation of the signal and backgrou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The previous studies of the collider measurements of the CPV in the Higgs Yukawa couplings can be found in refs. [82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99].…”
Section: A3 the Yukawa Couplings In The Cpv 2hdmmentioning
confidence: 99%
“…The previous studies of the collider measurements of the CPV in the Higgs Yukawa couplings can be found in refs. [82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99].…”
Section: A3 the Yukawa Couplings In The Cpv 2hdmmentioning
confidence: 99%
“…Moreover, some eccDNAs with low copy numbers or present in only a few cells cannot be detected using conventional bulk methods of eccDNA (4). In contrast, single-cell-based approaches can effectively overcome the above issues and provide deeper insights into the dynamic changes during the cell cycle, tracing its developmental process, cancer evolution (5,6), cellular functions, and regulation at the single-cell level (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, single-cell eccDNA research primarily relies on sequencing technologies, such as SMOOTH-seq (9), scEC&T-seq (6), scCircle-seq (5), and scGTP-seq (10). However, challenges such as enrichment difficulty due to the circular nature of eccDNA and cost constraints, have interfered with the development of standardized high-throughput technologies for single-cell eccDNA identification.…”
Section: Introductionmentioning
confidence: 99%